Half-duplex power beacon-assisted energy harvesting relaying networks: system performance analysis - Tan N. Nguyen; Minh Tran; Van-Duc Phan; Hoang-Nam Nguyen; Thanh-Long Nguyen (International Journal of Electrical and Computer Engineering (IJECE), 2019)
In this work, the half-duplex (HF) power beacon-assisted (PB) energy harvesting (EH) relaying network, which consists of a source (S), Relay (R), destination (D) and a power beacon (PB) are introduced and investigated. Firstly, the analytical expressions of the system performance in term of outage probability (OP) and the system throughput (ST) are analyzed and derived in both amplify-and-forward (AF) and decode-and-forward (DF) modes. After that, we verify the correctness of the analytical analysis by using Monte-Carlo simulation in connection with the primary system parameters. From the numerical results, we can see that all the analytical and the simulation results are matched well with each other.